Seabiscuit : the wonder horse - McCarthy, Meghan (New York : Simon & Schuster Books for Young Readers, 2008)
Seabiscuit, a funny looking horse with a losing streak, is bought and given a second chance by Charles Howard, and after new training and a loving jockey, Seabiscuit starts winning more races, but must prepare to run against War Admiral, the top racehorse in the country.
"A Paula Wiseman Book.".
Includes bibliographical references.
Booklist.
Bulletin (Center for Children's books).
School Library Journal starred.
3.8
Keywords: Horse racing -- United States -- Juvenile literature; Race horses -- United States -- Biography -- Juvenile literature; Seabiscuit (Race horse) -- Juvenile literature; Horse racing; Race horses; Seabiscuit (Race horse); Horse racing; Race horses -- Biography; Seabiscuit (Race horse)